Eurasian otter-human conflict in Koprulu Canyon National Park - Ahmet Koca; Bedirhan Eker; Yasin Ünal (Turkish Journal of Forestry)
The Eurasian otter (Lutra lutra) is the most widespread of the 13 otter species distributed in the world. It is known as our only semi-aquatic species belonging to the Mustalidae family and a nocturnal species. Its current distribution map covers many countries and regions. According to the IUCN (International Union for Conservation of Nature and Natural Resources) criteria, it was in the status of “Vulnerable (high risk of extinction in nature)” in the early 2000s, but since 2004 it has been changed to “Near Threatened (near threatened: likely to be defined as threatened in the near future)”. In our country, this species is also in the Near Threatened (NT) category. It is important to preserve the place of the otter, also known as an ecological indicator species, in biodiversity and transfer it to the future. The otter is on the list of fauna species under definitive protection of the BERN Convention. Although current populations are widespread, especially in Europe, the number of Eurasian otters is in great decline due to reasons such as environmental pollution and habitat loss. Wildlife is an important ecological indicator that provides information about the state of an ecosystem, and the presence of wildlife in an area provides information about structural deficiencies, cleanliness and pollution in an area, while revealing ecosystem success. Technology, population growth, pollution of air and water systems, forest fires, drying of water-rich areas used for agricultural purposes, chemical effects of pesticides used, and the pollution caused by these have a very negative effect on forest ecosystems and water wetlands. All necessary precautions should be taken to minimize the negative effects of these factors on otters, their species and habitats. In this article, the ecological importance of the Eurasian otter population, which is endangered according to IUCN Criteria, the findings obtained on the dangers it faces in Köprülü Canyon National Park and protection strategies will be shared. It is aimed to raise awareness of the public and necessary public institutions to support integrated control activities accepted worldwide for the sustainability of otters and wetlands.